Report on professional attachment with C Y Ng & Co. - Low, Kay Ngee. (2009)
This report gives a general idea of the working environment at the company, a summary of my working experience, as well as, a few insights I have gained during my attachment. As a concluding note, I have some recommendations, for the benefit of students due for the PA programme in the coming semesters.